EFEKTIVITAS KOMUNIKASI DALAM PROSES KEBIJAKAN IZIN PERTAMBANGAN RAKYAT PADA DINAS PERTAMBANGAN DAN ENERGI KABUPATEN KETAPANG - E.01109095, Yusnani (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Problems that occur in the implementation of Public Mining License is the ineffective communication made by the Department of Mines and Energy of Ketapang region to the society. Based on the research that has been done, it was revealed that the communication made were only in form of direct socialization in person and through announcements or circulars. The ineffectiveness of the communication gives effect to the implementation of the public mining license policy. This is exactly what makes people do not understand even not knowing about the importance of the public mining licenses. This article aims to describe the form of communication made by the Department of Mines and Energy of Ketapang in the process of the application of public mining license policy. The method used in this research is descriptive method in qualitative analysis. The result shows that public mining license policy implemented by the Department of Mines and Energy of Ketapang is good enough, but in terms of the implementation there are still shortcomings, such as lack of clarity and consistency, resulting in many illegal public mining were still. This writing aims to support the implementation of public mining license continues, so that people or institution, who do not have permission to do a mining can immediately apply for a mining permit peoplpublic mining license.Â Keywords: Public Mining License, Ineffective Communication, The Implementation of Public mining license